Agenesis of second premolar teeth - diagnostics and treatment - Smusz, Mirosław Piotr (Forum Ortodontyczne / Orthodontic Forum, 2018)
Agenesis of second premolar teeth represents a problem that dentists and orthodontists deal with on a daily basis, and which will occur with greater and greater prevalence due to a tendency for the number of teeth to decrease evolutionally. Besides being an obvious aesthetic defect, the absence of teeth may cause serious functional effects such as, for example, malocclusion. Depending on the author of a research study, agenesis prevalence rate is reported to amount to 0.3 – 36.5 per cent, which suggests that it is a problem that every orthodontist will, sooner or later, have to handle. Very delayed development of second premolars described in the literature may also cause serious problems. Aim. This article is an attempt to present the problem in its entirety. It will discuss patient diagnostics, treatment planning in cases where buds of second premolars are missing as well as common tooth anomalies in subjects from the sample under examination. Material and methods. Selected scientific articles from the years 1939-2015 have been reviewed. Results and conclusions. A clinician has at their disposal at least several tools allowing for separation of patients that can be found in a group being at risk of agenesis or late development of second premolar teeth. A clinician may refer to the chronological age, adjacent teeth development stage or certain phenotypic traits described. A diagnosis made correctly is the foundation of good treatment strategy, which has to take into account a large number of the abovementioned factors. The best choice in these days when full wide smiles are preferred seems to be to leave the deciduous tooth in place for as long as possible. (Smusz MP. Agenesis of second premolar teeth - diagnostics and treatment. Orthod Forum 2018; 14: 284-95).